BILIMLENDIRIW SAPASÍN TÁMIYINLEW HAQQÍNDA MÁMLEKET KEPILLIKLERI - Erejepov, M.; Maxsetova, X. (ILIM hám JÁMIYET, 2023)
The article contains valuable remarks of the President on the importance of improving the quality of education and knowledge, ensuring the education of young people, provided for by the Constitution, the regulation on education and other regulatory legal documents, as well as the Necessary recommendations for improving the education system.